The John Trot Fault: An English Dinner Table in the 1750s - Smith, Alice (Petits Propos Culinaires, 2024)
Many 18th century cookery books contain plates showing how dishes were arranged on the table. These range from the most elaborate (Charles Carter, The Complete Practical Cook, with 60 curious copper plates, 1730) to the engagingly simple illustrations, of which one shows a table with but two dishes on it, in Sarah Harrison’s The House-keeper’s pocket book (2nd ed’n corrected and improved, 1739). But it is rare to find an author who says anything which brings these plates to life and gives us an idea of what it was like to be a guest at a table so arrayed. Mrs Alice Smith has no plates in her Art of Cookery (1758) but she does provide some illuminating prose. Her book is very rare. Maclean, alone of the bibliographers, lists it; and she records only one publicly owned copy, in the New York Public Library. She also lists the edition of 1760, but only on the basis of a reference in the Scots Magazine of that year. Elizabeth David, who has a copy of the 1760 edition, has kindly allowed us to transcribe the relevant passage, which appears below.